(untitled) (Andamios, Revista de Investigación Social, 2009)
The present article exposes the results of four years of research on one of the social movements of unemployed people who arose in the last decade in Argentina: the CTD-Aníbal Verón. Analyzes the par-ticular coexistence in the interior of the CTD of clientelist mechanisms of social and political interaction, with new characteristics of identity and firmly structured around a social and political configuration that gives origin to this bound of identity, combining it with the territorial dimension in which the life of the organization ocurrs. For this, it approaches the analysis of the type of configuration and political roll that incarnates these expressions, their contradictory combinations between old and discredited political practices with novel forms to articulate the politician and the social thing in projects with objectives towards emancipation.